Binder for non-aqueous secondary battery electrodes, binder composition for non-aqueous secondary battery electrodes, non-aqueous secondary battery electrode and non-aqueous secondary battery

By using a polymer composed of (meth)acrylamide and nonionic ethylene conjugated units as the electrode binding agent of the non-aqueous secondary battery, the expansion and contraction of the electrode during the charging and discharging process is solved, and the high and low temperature characteristics, cycle characteristics and rate characteristics of the battery are improved.

JP2025068302APending Publication Date: 2025-04-28TOYO INK MFG CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023178098
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-10-16
Publication Date
2025-04-28

AI Technical Summary

Technical Problem

The materials bound to the electrodes of the existing non-aqueous secondary battery are difficult to meet the expansion and contraction needs of the electrodes during charging and discharging under the demands of high energy density and large capacity, resulting in a shortened battery life and an increase in internal resistance.

Method used

A polymer composed of (methacrylamide) and nonionic ethylene conjugated units is used as the electrode binding agent. The polymer has excellent electrolyte tolerance, stability and coating properties under specific proportions and structural designs.

Benefits of technology

The good performance of electrode binding agent under high and low temperature conditions is achieved, the high and low temperature characteristics, cycle characteristics and rate characteristics of the battery are improved, and the service life of the battery is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025068302000001
    Figure 2025068302000001
  • Figure 2025068302000002
    Figure 2025068302000002
  • Figure 2025068302000003
    Figure 2025068302000003
Patent Text Reader

Abstract

To provide a binder for non-aqueous secondary battery electrode improved in electrolyte resistance.SOLUTION: A binder for non-aqueous secondary battery electrodes contains a polymer (A1). The polymer (A1) is a polymer of an ethylenically unsaturated monomer mixture. The mixture contains (meth)acrylamide and a non-ionic ethylenically unsaturated monomer (a-1) of which a logarithm (Log Kow) of octanol / water distribution coefficient at 25°C is from 1.0 to 3.0. In the binder for non-aqueous secondary battery electrodes, when a mixture of which the volume ratio of ethylene carbonate and diethyl carbonate at 25°C is 2:3 is landed to a membrane consisting of the binder for non-aqueous secondary battery electrodes, a contact angle of the mixture of 0.5 μL after the lapse of 1 second from the landing is 5° to 40°at 25°C.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a binder for non-aqueous secondary battery electrodes that can be used to form a composite layer of an electrode of a non-aqueous secondary battery such as a lithium ion secondary battery, etc. The present invention also relates to a binder composition, a non-aqueous secondary battery electrode, and a non-aqueous secondary battery that contain the binder for non-aqueous secondary battery electrodes. [Background technology]

[0002] Non-aqueous secondary batteries are used in a wide range of applications because they are small, lightweight, have high energy density, and can be repeatedly charged and discharged. Among them, lithium-ion secondary batteries (hereinafter sometimes abbreviated as "LIB") are capable of obtaining high output, and are therefore used in mobile applications such as laptops and smartphones, as well as in automobiles.

[0003] The electrodes of secondary batteries are composed of an electrode active material (hereinafter sometimes abbreviated as "active material"), a conductive assistant, and a binder for binding these to a current collector. Conventionally, fluororesins such as polyvinylidene fluoride and polytetrafluoroethylene have been widely used as binders for secondary battery electrodes for both positive and negative electrodes. However, when a secondary battery is charged and discharged, the electrode repeatedly expands and contracts (hereinafter sometimes collectively referred to as "swelling and shrinking"), and if the active material or conductive assistant falls off from the electrode, it leads to a decrease in the battery life (number of charge and discharge cycles). Therefore, the binder for secondary battery electrodes is required to have cushioning properties that can withstand the swelling and shrinking of the electrode and adhesion to the current collector. However, fluororesins are insufficient in both cushioning properties that can follow the swelling and shrinking of the electrode and adhesion to the current collector. In addition, there is also the problem that fluororesins have restrictions on their use, such as being soluble only in specific solvents such as N-methylpyrrolidone.

[0004] In recent years, it has been reported that the cushioning and adhesion, which were drawbacks of fluororesins, have been improved by using water-dispersible binders such as styrene butadiene rubber (hereinafter sometimes abbreviated as "SBR") (Patent Document 1). However, SBR has poor oxidation resistance and swells significantly in commonly used electrolytes, which raises concerns that the permeation of ions is hindered and internal resistance increases.

[0005] Recently, there has been a demand for higher capacity batteries, and the use of silicon-based active materials that are expected to have high energy density as active materials has been considered. Silicon-based active materials swell and shrink more than conventional graphite-based active materials. Even if the SBR of Patent Document 1, which has high flexibility and can follow the swelling and shrinkage of conventional graphite-based active materials, is used as a binder, it cannot follow the swelling and shrinkage of silicon-based active materials, and the conductive paths between active materials are broken, and the internal resistance increases, which may reduce the battery performance.

[0006] Recently, therefore, polycarboxylic acid-based or polyacrylamide-based aqueous resins capable of following the swelling and shrinkage of active materials have been investigated (Patent Documents 2 to 4). However, when the aqueous resins of Patent Documents 2 to 4 are used as electrode binders, although the effect of suppressing the swelling and shrinkage of active materials can be expected, there are problems in that they have poor resistance to electrolyte (referred to as "electrolyte resistance" in this specification) and when used in batteries, the internal resistance increases, resulting in poor battery characteristics, and it is difficult to achieve battery performance over a wide temperature range from low to high temperatures. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] International Publication No. 2020 / 096287 [Patent Document 2] International Publication No. 2015 / 064464 [Patent Document 3] International Publication No. 2021 / 060737 [Patent Document 4] JP 2023-049937 A Summary of the Invention [Problem to be solved by the invention]

[0008] The problem to be solved by the present invention is to provide a binder for non-aqueous secondary battery electrodes having excellent electrolyte resistance. It is also to provide a binder composition for non-aqueous secondary battery electrodes containing the binder for non-aqueous secondary battery electrodes and having excellent solution stability and coatability. It is also to provide a non-aqueous secondary battery electrode having excellent adhesion and flexibility. It is also to provide a non-aqueous secondary battery having good rate characteristics, cycle characteristics, and high-temperature and low-temperature characteristics. [Means for solving the problem]

[0009] The present inventors have conducted extensive research to solve the above problems and have arrived at the present invention. That is, the present invention relates to a binder for a non-aqueous secondary battery electrode, which contains a polymer (A1), and the polymer (A1) is a polymer of an ethylenically unsaturated monomer mixture, which contains (meth)acrylamide and a nonionic ethylenically unsaturated monomer (a-1) having a logarithm of an octanol / water distribution coefficient (Log Kow) at 25° C. of 1.0 to 3.0, and when a mixed liquid consisting of ethylene carbonate and diethyl carbonate in a volume ratio of 2:3 at 25° C. is deposited on a film made of the binder for a non-aqueous secondary battery electrode, the contact angle of 0.5 μL of the mixed liquid 1 second after the deposition is 5° to 40° at 25° C.

[0010] The present invention also relates to the above binder for a nonaqueous secondary battery electrode, wherein the mixture contains 60 to 85 mass % of (meth)acrylamide and 15 to 40 mass % of a nonionic ethylenically unsaturated monomer (a-1) having a logarithm of an octanol / water partition coefficient (Log Kow) at 25° C. of 1.0 to 3.0, based on the total mass of the ethylenically unsaturated monomer mixture.

[0011] The present invention also relates to the above binder for a non-aqueous secondary battery electrode, wherein the mixture further contains 0.05 to 2 mass % of a reactive surfactant (a-2) having one or more unsaturated double bonds. (However, the above (a-2) excludes the above (a-1).)

[0012] The present invention also relates to the binder for a non-aqueous secondary battery electrode, wherein the polymer (A1) has an acid value of 100 mgKOH / g or less. Regarding.

[0013] In the present invention, the polymer (A1) has a storage modulus at 150° C. of 1.0×10 6 The binder for a non-aqueous secondary battery electrode has a viscosity of 100 Pa or more.

[0014] The present invention also relates to a binder composition for a non-aqueous secondary battery electrode, comprising the above-mentioned binder for a non-aqueous secondary battery electrode and a medium, wherein when the concentration of the polymer (A1) contained in the binder for a non-aqueous secondary battery electrode is 5 mass % in the composition, the binder composition for a non-aqueous secondary battery electrode has a transmittance of less than 70% at a wavelength of 400 nm.

[0015] The present invention also relates to a non-aqueous secondary battery electrode having a membrane containing the above-mentioned binder for a non-aqueous secondary battery electrode.

[0016] The present invention also relates to a non-aqueous secondary battery comprising the above-mentioned non-aqueous secondary battery electrode. Effect of the Invention

[0017] The present invention has made it possible to provide a binder for non-aqueous secondary battery electrodes that is excellent in electrolyte resistance. It has also made it possible to provide a binder composition for non-aqueous secondary battery electrodes that contains the binder for non-aqueous secondary battery electrodes and that is excellent in solution stability and coatability. It has also made it possible to provide a non-aqueous secondary battery electrode that is excellent in adhesion and flexibility. Furthermore, it has made it possible to provide a non-aqueous secondary battery that is excellent in high-temperature and low-temperature characteristics in addition to rate characteristics and cycle characteristics. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] The terms and symbols used in this specification are explained below. In this specification, a numerical range specified by "~" includes the numerical values ​​written before and after "~" as the range of the lower and upper limits. Furthermore, "film" and "sheet" are not distinguished by thickness. When "(meth)acrylamide" and "(meth)acrylate" are written, they respectively mean "acrylamide or methacrylamide" and "acrylate or methacrylate" unless otherwise specified. An ethylenically unsaturated monomer means a monomer having an ethylenically unsaturated double bond.

[0019] In this specification, the nonionic ethylenically unsaturated monomer (a-1) having a logarithm (Log Kow) of the octanol / water partition coefficient at 25° C. of 1.0 to 3.0, the reactive surfactant (a-2) having one or more unsaturated double bonds, the other ethylenically unsaturated monomer (a-3), the binder for a nonaqueous secondary battery electrode, the binder composition for a nonaqueous secondary battery electrode, the nonaqueous secondary battery, and the nonaqueous secondary battery may be abbreviated as the monomer (a-1), the reactive surfactant (a-2), the monomer (a-3), the binder, the binder composition, the electrode, and the battery, respectively. Note that the various components described in this specification may be used alone or in combination of two or more types, unless otherwise noted.

[0020] A nonaqueous secondary battery is a secondary battery that does not use water in the electrolyte, and examples of such batteries include lithium ion secondary batteries (LIBs), sodium ion secondary batteries, magnesium secondary batteries, etc. In this specification, LIBs are used as an example of a nonaqueous secondary battery, but it goes without saying that the binder for nonaqueous secondary battery electrodes, the binder composition for nonaqueous secondary battery electrodes, and the nonaqueous secondary battery electrodes of the present invention can be applied to nonaqueous secondary batteries other than LIBs.

[0021] <<Binder for non-aqueous secondary battery electrodes>> The binder for non-aqueous secondary battery electrodes contains a polymer (A1), and is characterized in that when a mixed liquid consisting of ethylene carbonate and diethyl carbonate in a volume ratio of 2:3 at 25°C is dropped onto a film made of the binder, the contact angle of 0.5μL of the mixed liquid 1 second after the drop is dropped is 5° to 40° at 25°C. The non-aqueous secondary battery binder composition containing the polymer (A1) and a medium is further mixed with an electrode active material to obtain a composite material slurry. By applying this composite material slurry to a current collector, a non-aqueous secondary battery electrode having a composite material layer on the current collector can be manufactured. In this specification, the composite material layer means a layer obtained by forming the composite material slurry into a layer by coating or the like and drying it.

[0022] <Polymer (A1)> The polymer (A1) is a polymer of an ethylenically unsaturated monomer mixture, and the mixture contains at least (meth)acrylamide and a monomer (a-1). The mixture preferably contains 0.05 to 2.0 mass% of a reactive surfactant (a-2), and may contain a monomer (a-3) as necessary. However, the reactive surfactant (a-2) is a monomer other than the monomer (a-1).

[0023] [(Meth)acrylamide] The (meth)acrylamide is contained in an amount of preferably 60 to 85 mass %, and more preferably 65 to 80 mass %, based on the total mass of the ethylenically unsaturated monomer mixture. By containing the binder in the above range, the electrolyte resistance of the binder can be significantly improved. In addition, when the binder is made into a composite slurry, the binder has good affinity with the active material and has excellent solution stability. Furthermore, the binder is prevented from swelling and shrinking, and has excellent battery characteristics such as rate characteristics and cycle characteristics.

[0024] [Nonionic ethylenically unsaturated monomer (a-1)] The monomer (a-1) has a logarithm of the octanol / water partition coefficient (Log Kow) at 25°C of 1.0 to 3.0, preferably 1.2 to 2.5. When the Log Kow is 1.0 or more, the polymer (A1) becomes a dispersion in an aqueous medium, and when it is made into a composite slurry, excellent coating properties are obtained. When it is applied to an electrode, the battery performance such as rate characteristics and cycle characteristics is improved. Furthermore, when the Log Kow is 3.0 or less, the adhesion to the current collector is also excellent. This is because the logarithm of the octanol / water partition coefficient (Log Kow) at 25°C of 1.0 to 3.0, preferably 1.2 to 2.5, suppresses the increase in viscosity even when the polymer (A1) is made into a high molecular weight, does not fill the gaps between the active materials, and improves the polymerizability with (meth)acrylamide.

[0025] In addition, the nonionic ethylenically unsaturated monomer is an ethylenically unsaturated monomer that does not have a charged functionality when in an aqueous medium, such as an ethylenically unsaturated monomer that does not have an amino group, a carboxy group, a sulfo group, or the like.

[0026] The content of the monomer (a-1) is preferably 15 to 40 mass %, more preferably 20 to 35 mass %, based on the total mass of the ethylenically unsaturated monomer mixture. When the content of the monomer (a-1) is 15 mass % or more, the flexibility of the electrode is excellent, and the cycle characteristics and low-temperature characteristics of the battery are excellent. In addition, even when the polymer (A1) has a high molecular weight, the viscosity is suppressed from increasing, and the coating property is excellent even when the mixture is made into a slurry. Furthermore, when the content of the monomer (a-1) is 40 mass % or less, the adhesion to the current collector is good, and the rate characteristics and cycle characteristics of the battery are also excellent.

[0027] Specific examples of the monomer (a-1) include: Linear or branched alkyl group-containing ethylenically unsaturated monomers such as ethyl acrylate (Log Kow=1.16), methyl methacrylate (Log Kow=1.27), propyl acrylate (Log Kow=1.67), ethyl methacrylate (Log Kow=1.78), t-butyl acrylate (Log Kow=2.06), isobutyl acrylate (Log Kow=2.09), butyl acrylate (Log Kow=2.23), propyl methacrylate (Log Kow=2.28), t-butyl methacrylate (Log Kow=2.67), and butyl methacrylate (Log Kow=2.84); Aromatic ethylenically unsaturated monomers such as benzyl acrylate (Log Kow=2.32), phenoxyethyl acrylate (Log Kow=2.44), and benzyl methacrylate (Log Kow=2.91); Cycloalkyl group-containing ethylenically unsaturated monomers such as cyclohexyl acrylate (Log Kow=2.62); Cycloalkenyl-containing ethylenically unsaturated monomers such as dicyclopentenyl acrylate (Log Kow=2.98); Alkoxy group-containing ethylenically unsaturated monomers such as methoxyethyl methacrylate; Ethylenically unsaturated monomers having two or more ethylenically unsaturated groups, such as ethylene glycol dimethacrylate (Log Kow=1.90), allyl methacrylate (Log Kow=2.10), 1,4-butanediol dimethacrylate (Log Kow=2.98), diallyl phthalate (Log Kow=3.00), etc.; alkoxysilyl group-containing ethylenically unsaturated monomers such as methacryloxypropyltrimethoxysilane (Log Kow=2.42); Epoxy group-containing ethylenically unsaturated monomers such as epoxycyclohexyl acrylate (Log Kow=1.78); Fluorinated alkyl group-containing ethylenically unsaturated monomers such as trifluoroethyl acrylate (Log Kow=1.57) and trifluoroethyl methacrylate (Log Kow=1.95); etc.

[0028] The monomer (a-1) preferably does not have a crosslinkable functional group, that is, it is preferably not a monomer having a crosslinkable functional group. The crosslinkable functional group is a functional group that gives a crosslinked structure to the side chain of the polymer, and includes a glycidyl group, an alkoxysilyl group, and an ethylenically unsaturated group. The monomer having a crosslinkable functional group includes a monomer having a glycidyl group, a monomer having an alkoxysilyl group, and a monomer having two or more ethylenically unsaturated bond groups.

[0029] From the viewpoints of good polymerization stability in an aqueous medium with (meth)acrylamide and good dispersibility of the polymer (A), the monomer (a-1) is preferably an ethylenically unsaturated monomer containing a linear or branched alkyl group, and more preferably methyl methacrylate and / or butyl (meth)acrylate.

[0030] The octanol / water partition coefficient (Log Kow) is expressed by the following (Formula 1), and is used as an index showing whether a certain compound X is more likely to be distributed into the water phase or the oil phase (octanol). The Log Kow of each ethylenically unsaturated monomer can also be calculated from experiments such as the shake flask method and HPLC method, but in this specification, it is a value calculated by converting the structural formula of the ethylenically unsaturated monomer into Smiles notation and inputting it using the YMB method (physical property prediction function) of the Hansen solubility parameter software HSPiP (ver.5.2.05). (Formula 1) Log Kow = Log(concentration of compound X in the octanol phase / concentration of compound X in the aqueous phase)

[0031] [Reactive surfactants (a-2) having one or more unsaturated double bonds] The reactive surfactant (a-2) refers to a surfactant capable of polymerizing with (meth)acrylamide and the nonionic ethylenically unsaturated monomer (a-1). Examples of the reactive surfactant (a-2) include anionic surfactants whose main skeleton is a sulfosuccinate ester, an alkyl ether, an alkyl phenyl ether, an alkyl phenyl ester, a (meth)acrylate sulfate ester, a phosphate ester, or the like; Nonionic surfactants whose main skeleton is an alkyl ether, an alkyl phenyl ether, an alkyl phenyl ester, or the like; Examples include: Among these, anionic surfactants are preferred because they provide good polymerization stability with (meth)acrylamide in an aqueous medium and good dispersibility of the polymer (A).

[0032] The content of the reactive surfactant (a-2) is preferably 0.05 to 2 mass%, more preferably 0.07 to 1 mass%, based on the total mass of the ethylenically unsaturated monomer mixture. When the reactive surfactant (a-2) is 0.05 mass% or more, the dispersibility of the polymer (A) is good, and when the mixture is made into a slurry, the solution stability and coatability are excellent. Furthermore, when the reactive surfactant (a-2) is 2 mass% or less, the adhesion to the current collector is good, and the rate characteristic and cycle characteristic are excellent. In one embodiment, the reactive surfactant (a-2) is preferably contained in an amount of 0.05 to 2 mass%, more preferably 0.07 to 1 mass%, of the total amount of (meth)acrylamide, monomer (a-1) and reactive surfactant (a-2) (100 mass%).

[0033] [Other ethylenically unsaturated monomers (a-3)] The monomer (a-3) refers to an ethylenically unsaturated monomer other than (meth)acrylamide, the monomer (a-1), and the reactive surfactant (a-2), which is polymerizable with (meth)acrylamide, the nonionic ethylenically unsaturated monomer (a-1), and the reactive surfactant (a-2).

[0034] Examples of the monomer (a-3) include Linear or branched alkyl group-containing ethylenically unsaturated monomers, such as methyl acrylate, hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, octyl (meth)acrylate, isononyl (meth)acrylate, isodecyl (meth)acrylate, lauryl (meth)acrylate, and isostearyl (meth)acrylate; Aromatic ethylenically unsaturated monomers such as phenoxyethyl methacrylate, styrene, and α-methylstyrene; cycloalkyl group-containing ethylenically unsaturated monomers, such as cyclohexyl methacrylate, dicyclopentanyl (meth)acrylate, and isobornyl (meth)acrylate; Cycloalkenyl-containing ethylenically unsaturated monomers such as dicyclopentenyl methacrylate; Alkoxy group-containing ethylenically unsaturated monomers such as methoxyethyl acrylate; Ethylenically unsaturated monomers having two or more ethylenically unsaturated groups, such as divinylbenzene and 1,9-nonanediol di(meth)acrylate; Hydroxyl group-containing ethylenically unsaturated monomers such as 2-hydroxyethyl (meth)acrylate and 4-hydroxybutyl acrylate; Amide group-containing ethylenically unsaturated monomers such as dimethylacrylamide, hydroxyacrylamide, isopropylacrylamide, and diacetoneacrylamide; Nitrile group-containing ethylenically unsaturated monomers such as (meth)acrylonitrile; Epoxy group-containing ethylenically unsaturated monomers such as glycidyl (meth)acrylate; Carboxy group-containing ethylenically unsaturated monomers such as (meth)acrylic acid; Examples include:

[0035] Among them, hydroxyethyl (meth)acrylate and / or (meth)acrylic acid are preferred as the monomer (a-3) from the viewpoints of the polymerization stability of (meth)acrylamide and the monomer (a-1) in an aqueous medium and the solution stability of the composite slurry mixed with the active material. When the monomer (a-3) is used in combination, the content of the monomer (a-3) is preferably 10% by mass or less based on the total mass (100% by mass) of the ethylenically unsaturated monomers.

[0036] When a mixed liquid of ethylene carbonate and diethyl carbonate in a volume ratio of 2:3 at 25° C. is dropped onto a film made of a binder for a nonaqueous secondary battery electrode containing polymer (A1), the contact angle of 0.5 μL of the mixed liquid 1 second after the drop is 5° to 40°, and preferably 5° to 30°, at 25° C. When the contact angle is within the above range, the electrolyte resistance of the binder for a nonaqueous secondary battery electrode is improved, the electrolyte penetrates well into the electrode, the internal resistance when used in a battery is suppressed, and the rate characteristics and cycle characteristics are good.

[0037] The acid value of the polymer (A1) is preferably 100 mgKOH / g or less, more preferably 20 mgKOH / g or less. By being in the above range, the solution stability when made into a composite material slurry is improved.

[0038] The storage modulus of the polymer (A1) at 150°C is 1.0 x 10 6 Pa or more, and 1.0×10 7 It is more preferable that the viscosity is 1.0×10 Pa or more. 10 It is preferably less than Pa. When the storage modulus is within the above range, the heat resistance is excellent when used in an electrode, and the cycle characteristics and high-temperature characteristics are good when used in a battery.

[0039] The polymer (A1) preferably has a swelling degree of less than 2 times, more preferably less than 1.5 times, when immersed for 72 hours at 60° C. in a mixed solution of ethylene carbonate and diethyl carbonate in a volume ratio of 2:3 at 25° C. Since the swelling degree is less than 2 times, the conductivity of lithium ions is not hindered by the swelling of the binder, and the rate characteristics and cycle characteristics of the battery are excellent.

[0040] [Method for producing polymer (A1)] The method for polymerizing the ethylenically unsaturated monomer to produce the polymer (A1) may be any method such as solution polymerization, suspension polymerization, bulk polymerization, or emulsion polymerization. The reactive surfactant (a-2) is preferably used together with the ethylenically unsaturated monomer mixture when polymerizing the polymer (A1). By using the reactive surfactant during polymerization, the polymerization stability of the (meth)acrylamide and the monomer (a-1) in the aqueous medium is excellent. The solid content concentration of the polymer (A1) in the binder composition is not particularly limited, but is preferably from 7% by mass to 50% by mass.

[0041] As the radical polymerization initiator used in the polymerization reaction, a known oil-soluble polymerization initiator or an aqueous polymerization initiator can be used. The radical polymerization initiator is preferably used in an amount of 0.1 to 1.0 part by mass, more preferably 0.1 to 0.4 part by mass, based on 100 parts by mass of the mixture of ethylenically unsaturated monomers. By using the radical polymerization initiator in the above range, the viscosity of the binder composition can be adjusted within an appropriate range, and the binder composition has excellent heat resistance, adhesion, and coatability.

[0042] The oil-soluble polymerization initiator is not particularly limited, and examples thereof include organic peroxides such as benzoyl peroxide, tert-butyl peroxybenzoate, tert-butyl hydroperoxide, tert-butyl peroxy(2-ethylhexanoate), tert-butylperoxy-3,5,5-trimethylhexanoate, and di-tert-butyl peroxide; and azobis compounds such as 2,2'-azobisisobutyronitrile, 2,2'-azobis-2,4-dimethylvaleronitrile, 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile), and 1,1'-azobis-cyclohexane-1-carbonitrile.

[0043] In the polymerization, it is preferable to use an aqueous polymerization initiator. As the aqueous polymerization initiator, for example, conventionally known ones such as ammonium persulfate (APS), potassium persulfate (KPS), hydrogen peroxide, and 2,2'-azobis(2-methylpropionamidine) dihydrochloride can be suitably used.

[0044] In the polymerization, a reducing agent may be used in combination with the polymerization initiator. The use of a reducing agent in combination accelerates the emulsion polymerization rate and facilitates polymerization at low temperatures. Examples of the reducing agent include reducing organic compounds such as ascorbic acid, erythorbic acid, tartaric acid, citric acid, glucose, and metal salts of formaldehyde sulfoxylate; reducing inorganic compounds such as sodium thiosulfate, sodium sulfite, sodium bisulfite, and sodium metabisulfite; ferrous chloride, Rongalite, and thiourea dioxide. The reducing agent is preferably used in an amount of 0.05 to 4 parts by mass based on 100 parts by mass of the ethylenically unsaturated monomer.

[0045] When polymerizing the ethylenically unsaturated monomer, a buffering agent, a chain transfer agent, a basic compound, etc. may be used, if necessary. Examples of buffers include sodium acetate, sodium citrate, and sodium bicarbonate. Examples include: Examples of the chain transfer agent include n-octyl mercaptan, t-octyl mercaptan, n-nonyl mercaptan, t-nonyl mercaptan, n-decyl mercaptan, t-decyl mercaptan, n-undecyl mercaptan, t-undecyl mercaptan, n-dodecyl mercaptan, t-dodecyl mercaptan, n-tridecyl mercaptan, t-tridecyl mercaptan, n-tetradecyl mercaptan, t-tetradecyl mercaptan, n-heptadecyl mercaptan, t-heptadecyl mercaptan, t-hexadecyl mercaptan, and n-hexadecyl mercaptan. The basic compound is a compound used for neutralization. Examples of the basic compound include: Examples of the amines include alkylamines such as trimethylamine, triethylamine, and butylamine, alcoholamines such as 2-dimethylaminoethanol, diethylaminoethanol, diethanolamine, triethanolamine, and aminomethylpropanol, morpholine, and ammonia.

[0046] In addition, a non-reactive surfactant having no unsaturated double bond can be used as long as it does not adversely affect the physical properties of the composite slurry or the electrode. The ionic species of the non-reactive surfactant include anionic, cationic, and nonionic, with anionic and nonionic being preferred.

[0047] Examples of the anionic surfactant include higher fatty acid salts such as sodium oleate, alkylarylsulfonates such as dodecylbenzenesulfonic acid, alkyl sulfates such as sodium lauryl sulfate, polyoxyethylene alkyl ether sulfates such as sodium polyoxyethylene lauryl ether sulfate, alkyl sulfosuccinates such as sodium monooctyl sulfosuccinate, sodium dioctyl sulfosuccinate, and sodium polyoxyethylene lauryl sulfosuccinate, and derivatives thereof, and polyoxyethylene distyrenated phenyl ether sulfate.

[0048] Examples of nonionic surfactants include polyoxyethylene alkyl ethers such as polyoxyethylene lauryl ether and polyoxyethylene stearyl ether, polyoxyethylene alkyl phenyl ethers such as polyoxyethylene octyl phenyl ether and polyoxyethylene nonyl phenyl ether, sorbitan higher fatty acid esters such as sorbitan monolaurate, sorbitan monostearate and sorbitan trioleate, polyoxyethylene sorbitan higher fatty acid esters such as polyoxyethylene sorbitan monolaurate and polyoxyethylene sorbitan monostearate, polyoxyethylene higher fatty acid esters such as polyoxyethylene monolaurate and polyoxyethylene monostearate, glycerin higher fatty acid esters such as oleic acid monoglyceride and stearic acid monoglyceride, polyoxyethylene-polyoxypropylene block copolymers, polyvinyl alcohol, polyvinylpyrrolidone, polyoxyethylene distyrenated phenyl ether, and the like.

[0049] <<Binder composition for non-aqueous secondary battery electrodes>> The non-aqueous secondary battery binder composition includes a polymer (A1) and a medium. The binder composition for a non-aqueous secondary battery electrode of the present invention has a transmittance at a wavelength of 400 nm when the concentration of the polymer (A1) is 5% by mass of less than 70%, preferably less than 60%. By being in the above range, the dispersibility of the binder in the medium is sufficiently ensured, and when a composite slurry is formed, the gaps between the active materials are not filled, and the ion permeability of the electrode is good. This suppresses the internal resistance, and improves the battery performance such as the rate characteristic and the cycle characteristic. In addition, even when the binder has a high molecular weight, the increase in viscosity is suppressed, and the coatability when a composite slurry is formed is improved.

[0050] The transmittance can be calculated by dividing the light source into measurement wavelengths using a diffraction grating and calculating the ratio of light (l) that is transmitted through the sample to the light (l0) that is incident on the sample, and is expressed by the following (Equation 2). (Formula 2) Transmittance (%)=(l / l0)×100

[0051] The binder composition for non-aqueous secondary battery electrodes preferably has a viscosity of 1,500 mPa·s or more and less than 20,000 mPa·s, more preferably 2,500 mPa·s or more and less than 10,000 mPa·s, under the condition of a solid content concentration of 15% by mass. By being within the above numerical range, the composition has a sufficient molecular weight to exhibit adhesion to a current collector, and is excellent in solution stability and coatability when mixed with an active material. That is, the binder composition of the present invention is in a dispersed state, so that the interaction between the polymers (A1) is suppressed, and the composition has a high molecular weight but is excellent in handling, such as coatability. The viscosity can be determined by measuring the viscosity using a B-type viscometer at 25°C, at a rotation speed of 20 rpm, and for a rotation time of 60 seconds.

[0052] <medium> The medium may be an aqueous dispersion medium or an aqueous solvent. It is preferable to use water as the medium, but an aqueous solvent may be used as necessary. Examples of the aqueous solvent include alcohols, glycols, cellosolves, amino alcohols, amines, ketones, carboxylic acid amides, phosphoric acid amides, sulfoxides, carboxylic acid esters, phosphoric acid esters, ethers, and nitriles.

[0053] <Optional ingredients> The binder composition of the present invention may contain various additives such as an antifoaming agent, a leveling agent, a preservative, a crosslinking agent, a dispersant, and a binder as other optional components within a range that does not impair the effects of the present invention.

[0054] The binder composition for non-aqueous secondary battery electrodes of the present invention can be used in the negative and positive electrodes of non-aqueous secondary batteries, as well as in energy devices, such as capacitors and solar cells.

[0055] 《Nonaqueous secondary battery electrode》 The non-aqueous secondary battery electrode of the present invention can be produced by applying a composite slurry, in which an electrode active material is mixed with a battery binder composition, to a current collector and drying the mixture. The non-aqueous secondary battery electrode of the present invention has a film containing the non-aqueous secondary battery electrode binder of the present invention. The film contains preferably 0.1 to 20 parts by mass, more preferably 0.5 to 10 parts by mass of the binder per 100 parts by mass of the electrode active material.

[0056] <Electrode active material> The positive electrode active material is not particularly limited, but for example, in the case of LIB, it is preferable that it is a metal compound such as a metal oxide or metal sulfide that can reversibly dope or intercalate lithium ions. For example, lithium manganese composite oxide (e.g., Li X Mn2O4 or Li X MnO2), lithium nickel composite oxide (e.g. Li X NiO2), lithium cobalt complex oxide (Li X CoO2), lithium nickel cobalt complex oxide (e.g. Li X Ni 1-y Co y O2), lithium manganese cobalt complex oxide (e.g. Li X Mn y Co 1-y O2), lithium nickel manganese cobalt composite oxide (e.g. Li X Ni y Co z Mn 1-y-z O2), spinel-type lithium manganese nickel composite oxide (e.g. Li X Mn 2-y Ni y O4), lithium phosphate powder with an olivine structure (e.g. Li X FePO4, Li X Fe 1-y Mn y PO4, Li X CoPO4, etc.), manganese oxide, iron oxide, copper oxide, nickel oxide, vanadium oxide (e.g. V2O5, V6O 13) Examples include transition metal oxide powders such as titanium oxide, transition metal sulfide powders such as iron(III) sulfate (Fe2(SO4)3), TiS2, and FeS. However, x, y, and z are numbers, where 0 < x < 1, 0 < y < 1, 0 < z < 1, and 0 < y + z < 1. These cathode active materials can also be used alone or in combination of two or more.

[0057] The anode active material is not particularly limited. For example, in the case of a LIB, metallic Li and its alloys, tin alloys, silicon alloy anodes, which can reversibly dope or intercalate lithium ions, X TiO2, Li X Fe2O3, Li X Fe3O4, Li X Metal oxide systems such as WO2, conductive polymers such as polyacetylene and poly-p-phenylene, artificial graphite such as highly graphitized carbon materials, or carbonaceous powders such as natural graphite, and resin-fired carbon materials can be used. However, x is a number, where 0 < x < 1. These anode active materials can also be used alone or in combination of two or more.

[0058] The binder slurry preferably contains a conductive aid in combination with the electrode active material. Examples of the conductive aid include nickel powder, cobalt oxide, titanium oxide, carbon, etc. Examples of carbon include acetylene black, furnace black, graphite, carbon fiber, carbon nanotube, fullerenes. The amount of the conductive aid used is preferably 0.03 to 10 parts by mass with respect to 100 parts by mass of the electrode active material.

[0059] <Current collector> The material and shape of the current collector used for forming the electrode are not particularly limited and can be appropriately selected. Examples of the material of the current collector include conductive metals or alloys such as aluminum, copper, nickel, titanium, and stainless steel. In addition, as the shape, generally a flat foil is used, but a current collector with a roughened surface, a perforated foil-shaped current collector, or a mesh-shaped current collector can also be used. The thickness of the current collector is preferably about 0.5 to 30 μm.

[0060] To form a non-aqueous secondary battery electrode, the composite slurry is applied to a current collector, heated, and dried. The composite slurry can be applied using any coater head such as a reverse roll method, a comma bar method, a gravure method, or an air knife method, and the dryer can be a blower dryer, a hot air dryer, an infrared heater, or a far infrared heater.

[0061] 《Non-aqueous secondary battery》 The non-aqueous secondary battery of the present invention includes the non-aqueous secondary battery electrode of the present invention. As the electrolyte used in the non-aqueous secondary battery, various conventionally known electrolytes capable of moving ions can be used. For example, those containing lithium salts such as LiBF4, LiClO4, LiPF6, LiAsF6, LiSbF6, LiCF3SO3, Li(CF3SO2)2N, LiC4F9SO3, Li(CF3SO2)3C, LiI, LiBr, LiCl, LiAlCl, LiHF2, LiSCN, or LiBPh4 (wherein Ph is a phenyl group) can be used, but are not limited thereto. The electrolyte is preferably dissolved in a non-aqueous solvent and used as an electrolytic solution.

[0062] Examples of non-aqueous solvents include, but are not limited to, carbonates such as ethylene carbonate, propylene carbonate, butylene carbonate, dimethyl carbonate, ethyl methyl carbonate, and diethyl carbonate; lactones such as γ-butyrolactone, γ-valerolactone, and γ-octanoic lactone; glymes such as tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane, 4-methyl-1,3-dioxolane, 1,2-methoxyethane, 1,2-ethoxyethane, and 1,2-dibutoxyethane; esters such as methyl formate, methyl acetate, and methyl propionate; sulfoxides such as dimethyl sulfoxide and sulfolane; and nitriles such as acetonitrile. These solvents may be used alone or in combination of two or more.

[0063] It is also preferable to use the electrolyte as a polymer electrolyte in the form of a gel held in a polymer matrix, such as an acrylic resin having a polyalkylene oxide segment, a polyphosphazene resin having a polyalkylene oxide segment, or a polysiloxane resin having a polyalkylene oxide segment.

[0064] The non-aqueous electrolyte secondary battery preferably includes a separator, such as, but not limited to, polyethylene nonwoven fabric, polypropylene nonwoven fabric, polyamide nonwoven fabric, and nonwoven fabrics obtained by subjecting these to hydrophilic treatment.

[0065] The structure of the nonaqueous secondary battery of the present embodiment is not particularly limited, but typically includes a positive electrode and a negative electrode, and a separator that is provided as necessary, and can have various shapes depending on the purpose of use, such as a paper type, a cylindrical type, a button type, a laminated type, etc.

[0066] The nonaqueous secondary battery using the above-mentioned components is excellent in safety and battery characteristics. The nonaqueous secondary battery of the present invention can be used for industrial, in-vehicle and mobile applications. EXAMPLES

[0067] The present invention will be described in more detail below with reference to the following examples, which are not intended to limit the scope of the present invention. Unless otherwise specified, "parts" means "parts by mass," "%" means "% by mass," the values ​​in the tables are solid content masses, and blanks indicate that no space is used.

[0068] <Production of binder dispersion for non-aqueous secondary battery electrodes> [Example X-1] A mixture was obtained by mixing 70 parts of acrylamide, 2 parts of methacrylamide, 14 parts of methyl methacrylate, 7 parts of butyl acrylate, 5 parts of 2-hydroxyethyl acrylate, 2 parts of 2-ethylhexyl acrylate, 1.0 parts of 20% Adeka Reasoap SR-10 aqueous solution (0.2 parts as solids), and 90 parts of water. 450 parts of water and 30 parts of the above mixture were charged into a reaction vessel equipped with a stirrer, a thermometer, a dropping funnel, and a reflux condenser. Next, the internal temperature of the reaction vessel was raised to 80°C and nitrogen substitution was sufficiently performed, and then 1.8 parts of a 10% aqueous ammonium persulfate solution (0.18 parts as solids) was added as an initiator to start the reaction. While maintaining the internal temperature at 80°C, the remaining mixture was dropped over 60 minutes. After the dropwise addition was completed, the reaction was continued at 80°C for another 3 hours, and after confirming that the conversion rate exceeded 98% by solids measurement, the mixture was cooled to 30°C. Water was added to adjust the solid content to 15%, to obtain a non-aqueous secondary battery electrode binder dispersion containing the polymer (A1-1). The solid content was determined from the baking residue at 150° C. for 20 minutes.

[0069] [Examples X-2 to X-20, Comparative Examples X-1 to X-4] A non-aqueous secondary battery electrode binder dispersion containing polymers (A1-2 to A1-24) was obtained in the same manner as in Example X-1, except that the blending composition and blending amount (parts by mass) shown in Table 1 were used. In addition, for Examples X-2, 4, 5, 17, and 18 and Comparative Examples X-1 and 4, after the reaction was completed, 25% ammonia water was added to the polymer in an equimolar amount relative to the carboxyl groups to neutralize the mixture. The physical properties and evaluation results of the obtained non-aqueous secondary battery electrode binder were determined by the following methods. The results are shown in Table 1.

[0070] <Acid value> The acid value of the binder is the number of milligrams of potassium hydroxide required to neutralize the acidic components contained in 1 g of dried binder. It was calculated by potentiometric titration using a potassium hydroxide-ethanol solution using an automatic titrator (HIRANUMA's "COM-A19") according to the method specified in JIS K2501.

[0071] <Contact angle> Binder dispersion is applied to the glass substrate at a dry weight of 50 g / m 2 The mixture was applied with an applicator so that the thickness of the binder was 100 μm, and then dried at 40° C. for 24 hours to prepare a coating film made of a binder. A mixed liquid of ethylene carbonate and diethyl carbonate in a volume ratio of 2:3 at 25° C. was dropped onto the coated surface of the coating film using an automatic contact angle measuring device (DM-501 manufactured by Kyowa Interface Co., Ltd.) at 25° C., and the contact angle was measured 1 second after the drop had landed. A: Contact angle is 5°~30°. B: Contact angle greater than 30° and less than 40°. C: Contact angle is less than 5° or more than 40°.

[0072] <Transmittance> The obtained binder dispersion was adjusted to a solids concentration of 5% with water, placed in a quartz cell with an optical path length of 1 cm, and the transmittance at a wavelength of 400 nm was measured using a spectrophotometer ("V-770" manufactured by JASCO Corporation). Water was used as a comparison. A:Transmittance is less than 60%. B: Transmittance is 60% or more and less than 70%. C: Transmittance is 70% or more.

[0073] <Storage modulus> The obtained binder dispersion was dried at 40°C for 72 hours to prepare a film with a thickness of about 0.5 mm. The obtained film was cut into a rectangular shape with a width of 5 mm and a length of 20 mm to prepare a sample, and the storage modulus at 150°C was measured using a dynamic viscoelasticity measuring device ("DVA-200" manufactured by IT Measurement and Control Co., Ltd.). The measurement conditions were as follows. Measurement mode: Tensile Frequency: 10Hz Distortion: 0.01% Heating condition: 10℃ / min A: Storage modulus is 1.0×10 7 More than Pa. B: Storage modulus is 1.0×10 6 Above 1.0×10 7 Less than Pa. C: Storage modulus is 1.0×10 6 Less than Pa.

[0074] <Viscosity> The viscosity of the obtained binder dispersion having a solid content concentration of 15% was measured using a B-type viscometer (Toki Sangyo Co., Ltd., "TVB-10") (temperature: 25°C, spindle rotation time: 60 seconds, spindle rotation speed: 20 rpm). A: Viscosity is 2,000 or more and less than 7,000 mPa·s. B: Viscosity is 1,000 or more and less than 2,000 mPa·s. B': Viscosity is 7,000 or more and less than 15,000 mPa·s. C: Viscosity less than 1,000 mPa s C': Viscosity is 15,000 mPa·s or more.

[0075] Evaluation of binder dispersion <Electrolyte resistance> The electrolyte resistance is the ease with which a polymer dissolves and swells in an electrolyte, and was evaluated based on the degree of swelling determined by the following method. The smaller the degree of swelling, the better the electrolyte resistance. The obtained binder dispersion was dried at 40°C for 72 hours to prepare a film with a thickness of about 1 mm. Then, this film was cut into a size of 10 mm length x 10 mm width to prepare a sample, which was then immersed in a mixed solvent of ethylene carbonate and diethyl carbonate in a volume ratio of 2:3 at 25°C at 60°C for 72 hours. The swelling degree of the film before and after immersion was calculated as follows. Swelling degree (times): = (mass of sample after immersion) / (mass of sample before immersion) A: The degree of swelling is less than 1.5 times. B: Swelling degree is 1.5 times or more but less than 2 times. C: Swelling degree is more than double.

[0076] The abbreviations in the table are as follows: The Log Kow value of the ethylenically unsaturated monomer was calculated by converting the structural formula of the ethylenically unsaturated monomer into Smiles notation and inputting it using the YMB method (physical property prediction function) of the Hansen Solubility Parameter software HSPiP (ver.5.2.05). <Nonionic ethylenically unsaturated monomer (a-1)> EA: Ethyl acrylate (Log Kow 1.16) MMA: Methyl methacrylate (Log Kow 1.27) EMA: Ethyl methacrylate (Log Kow 1.78) BA: Butyl acrylate (Log Kow 2.23) BzMA: Benzyl methacrylate (Log Kow 2.91) <Reactive surfactant (a-2)> SR-10: Adeka Reasoap SR-10 (anionic surfactant manufactured by ADEKA Corporation) PD-104: LATEMURU PD-104 (anionic surfactant manufactured by Kao Corporation) KH-10: Aqualon KH-10 (anionic surfactant manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) <Monomer (a-3)> AA: Acrylic acid 2HEA: 2-hydroxyethyl acrylate MA: Methyl acrylate St: styrene 2EHA: 2-Ethylhexyl acrylate EGDMA: Ethylene glycol dimethacrylate <Non-reactive surfactant> 2FG: Emeral 2FG (Kao Corporation)

[0077] [Table 1]

[0078] [Table 1]

[0079] <Preparation of negative electrode composite material slurry (1)> [Example y-1] Capacity 150cm 3In a plastic container, 0.5 parts of acetylene black (Denka Black (registered trademark) HS-100, manufactured by Denka) as a conductive assistant, 1 part of carboxymethylcellulose (Carboxymethylcellulose #1190 manufactured by Daicel FineChem, 100% non-volatile content, hereinafter abbreviated as "CMC") as a thickener, and 98.4 parts of water were mixed, and then stirred at 2,000 rpm for 30 seconds using a centrifugal mixer (Thinky Corporation, Awatori Rentaro, ARE-310). Then, 97 parts of artificial graphite (Nippon Graphite Industries, CGB-20, 100% non-volatile content, hereinafter abbreviated as "artificial graphite A") was added as a negative electrode active material, and the mixture was stirred at 2,000 rpm for 150 seconds using the mixer. Then, 10 parts of a binder dispersion for a non-aqueous secondary battery electrode containing the polymer (A1-1) obtained in Example X-1 as a binder was added, and the mixture was stirred at 2,000 rpm for 30 seconds using the mixer to obtain a non-aqueous secondary battery negative electrode composite slurry.

[0080] [Examples y-2 to 20, Comparative Examples y-1 to 4] Except for changing the composition shown in Table 2, a mixture slurry for a non-aqueous secondary battery negative electrode was obtained in the same manner as in Example y-1.

[0081] <Preparation of negative electrode composite material slurry (2)> [Example y-21] Capacity 150cm 3In a plastic container, 0.5 parts of acetylene black (Denka Black (registered trademark) HS-100, manufactured by Denka) as a conductive assistant, 1 part of CMC as a thickener, and 98.4 parts of water were mixed, and then stirred for 30 seconds at 2,000 rpm using a centrifugal mixer (Thinky's Awatori Rentaro, ARE-310). Then, 87 parts of artificial graphite A and 10 parts of a silicon-based active material (Osaka Titanium Technology's SILICON MONOOXIDE SiO 1.3C 5μm, non-volatile content 100%, hereinafter abbreviated as "silicon A") were added as negative electrode active materials, and the mixture was stirred for 150 seconds at 2,000 rpm using the mixer. Then, 10 parts of a binder dispersion for a non-aqueous secondary battery electrode containing the polymer (A1-1) obtained in Example X-1 as a binder was added, and the mixture was stirred at 2,000 rpm for 30 seconds using the mixer to obtain a non-aqueous secondary battery negative electrode composite slurry.

[0082] [Examples y-22 to 44, Comparative Examples y-5 to 8] Except for changing the blending composition to that shown in Table 2, a mixture slurry for a nonaqueous secondary battery negative electrode was obtained in the same manner as in Example y-21.

[0083] <Preparation of negative electrode> [Example Y-1] The negative electrode composite slurry obtained in Example y-1 was applied onto a copper foil having a thickness of 20 μm using an applicator, and then dried in an electric oven at 120° C.±5° C. for 25 minutes to form a composite layer. The composite layer was then rolled using a roll press (3 ton hydraulic roll press, manufactured by Sun Metals) to obtain a negative electrode. The weight per unit area of ​​the composite layer was 10 mg / cm. 2 The density of the composite layer after rolling is 1.6 g / cm 3 It was.

[0084] [Examples Y-2 to 44, Comparative Examples Y-1 to 8] Except for changing the negative electrode composite slurry shown in Table 2, a nonaqueous secondary battery negative electrode was obtained in the same manner as in Example Y-1.

[0085] Evaluation of the composite slurry <Solution stability> The composite slurry was stored at 50° C. and visually observed for the presence or absence of aggregation, precipitation, or separation. [Evaluation Criteria] ⊚: No aggregation, precipitation or separation was observed for 2 weeks or more after the start of storage. Extremely good. ○: Any of aggregation, precipitation, or separation was observed within 1 week or more and less than 2 weeks from the start of storage. Good. △: Either aggregation, precipitation or separation was observed within 4 days or more but less than 1 week from the start of storage. Usable. ×: Any of aggregation, precipitation, or separation was observed within 3 days of storage. Not usable.

[0086] <Coatability> The coating properties of the slurry mixture when applied onto the copper foil were visually observed. [Evaluation Criteria] : The coating thickness is uniform and there is no repellency. Very good. ○: Unevenness or repellency is observed in less than 5% of the coated area. Good. △: There is unevenness or repellency in 5% or more but less than 10% of the coated area. Usable. ×: Unevenness or repellency is observed in 10% or more of the coated area. Not suitable for use.

[0087] <Evaluation of the negative electrode> <Adhesion> The adhesion was evaluated by a 180-degree peel test using the obtained negative electrode. Two 90 mm x 20 mm rectangles were cut out with the coating direction of the negative electrode as the long axis. A tabletop tensile tester (Strograph E3, manufactured by Toyo Seiki Seisakusho Co., Ltd.) was used to evaluate the adhesion by a 180-degree peel test. Specifically, a double-sided tape (No. 5000NS, manufactured by Nitto) measuring 100 mm x 30 mm was attached to a stainless steel plate, and the composite layer side of the prepared negative electrode was adhered to the other side of the double-sided tape to prepare a test sample. Next, the test sample was fixed vertically so that the short sides of the rectangle were at the top and bottom, and the end of the copper foil was pulled from the bottom to the top at a constant speed (50 mm / min) while being peeled off, and the average value of the stress at this time was taken as the peel strength. Judgment criteria ◎: 0.5N / cm or more. Extremely good. ○: 0.3N / cm or more and less than 0.5N / cm. Good. △: 0.1N / cm or more and less than 0.3N / cm. Usable. ×: Less than 0.1N / cm. Not suitable for use.

[0088] <Flexibility> The flexibility of the negative electrode was evaluated by the following method. The obtained negative electrode was cut into a size of 10 mm wide x 50 mm long to prepare a sample. The sample was wrapped around a metal rod with a diameter of 1.0 mm so that it was in contact with the current collector side. In this state, the surface state of the composite layer was visually observed, and the flexibility was evaluated according to the following evaluation criteria. ⊚: No change was observed on the surface of the composite layer. Very good. ◯: Changes were observed in part of the surface of the composite layer. Good. △: Cracks were observed in part of the surface of the composite layer. Usable. ×: Cracks were observed over the entire surface of the composite layer. Unusable.

[0089] <Preparation of positive electrode composite slurry> [Example y-45] Capacity 150cm 3 In a plastic container, 0.5 parts of acetylene black (Denka Black (registered trademark) HS-100, manufactured by Denka) as a conductive assistant, 1 part of carboxymethylcellulose (Carboxymethylcellulose #1190, manufactured by Daicel FineChem, non-volatile content 100%, hereinafter abbreviated as "CMC") as a thickener, and 32.5 parts of water were mixed, and then stirred for 30 seconds at 2,000 rpm using a centrifugal mixer (Thinky Corporation's Awatori Rentaro, ARE-310). Thereafter, 97 parts of lithium iron phosphate HED (trademark) LFP-400, manufactured by BASF, non-volatile content 100%, hereinafter abbreviated as "LFP") was added as a positive electrode active material, and the mixture was stirred for 150 seconds at 2,000 rpm using the mixer. Then, 10 parts of a binder dispersion for a non-aqueous secondary battery electrode containing the polymer (A1-1) obtained in Example X-1 as a binder was added, and the mixture was stirred at 2,000 rpm for 30 seconds using the mixer to obtain a non-aqueous secondary battery positive electrode composite slurry.

[0090] [Examples y-46, 47, Comparative Examples y-9 to 11] Except for changing the materials and the amounts of the materials to those shown in Table 2, a nonaqueous secondary battery positive electrode composite slurry was obtained in the same manner as in Example y-45.

[0091] <Preparation of positive electrode> [Example Y-45] The positive electrode composite slurry obtained in Example y-45 was applied onto an aluminum foil having a thickness of 20 μm using an applicator, and then dried in an electric oven at 120°C ± 5°C for 25 minutes to form a composite layer. The composite layer was then rolled using a roll press (3t hydraulic roll press, manufactured by Sun Metals) to obtain a positive electrode. The weight per unit area of ​​the composite layer was 20 mg / cm. 2 The density of the composite layer after rolling is 2.1 g / cm 3 It was.

[0092] [Examples Y-46, 47, Comparative Examples Y-9 to 11] A nonaqueous secondary battery positive electrode was obtained in the same manner as in Example Y-41, except that the positive electrode composite slurry shown in Table 2 was used.

[0093] Positive evaluation <Adhesion> The adhesion was evaluated in the same manner as for the negative electrode, except that the judgment criteria were different from those for the negative electrode and were based on the following criteria. Judgment criteria ◎: 1N / cm or more. Extremely good. ○: 0.5N / cm or more and less than 1N / cm. Good. △: 0.3N / cm or more and less than 0.5N / cm. Usable. ×: Less than 0.3N / cm. Not available.

[0094] <Flexibility> The flexibility was evaluated in the same manner as in the case of the negative electrode.

[0095] [Table 2]

[0096] [Table 2]

[0097] [Table 2]

[0098] (Preparation of standard negative electrode) Capacity 150cm 3 In a plastic container, 0.5 parts of acetylene black (Denka Black (registered trademark) HS-100, manufactured by Denka) as a conductive assistant, 1 part of CMC, and 98.4 parts of water were mixed, and then the mixture was stirred for 30 seconds at 2,000 rpm using a centrifugal mixer (Thinky's Awatori Rentaro, ARE-310). Furthermore, 87 parts of artificial graphite A and 10 parts of silicon A were added as negative electrode active materials, and the mixture was stirred for 150 seconds at 2,000 rpm using the above mixer. Next, 3.1 parts of SBR (JSR's TRD2001) were added as a binder, and the mixture was stirred for 30 seconds at 2,000 rpm using the above mixer, to obtain a standard negative electrode composite composition.

[0099] The obtained standard negative electrode composite composition was applied to a copper foil having a thickness of 20 μm as a current collector using an applicator, and then dried in an electric oven at 80°C ± 5°C for 25 minutes to obtain an electrode with a coating weight per unit area of ​​10 mg / cm. 2 Further, a rolling process was performed using a roll press (Thank Metal, 3 ton hydraulic roll press) to adjust the density of the composite layer to 1.6 g / cm. 3 A standard negative electrode was prepared.

[0100] (Preparation of standard positive electrode) Capacity 150cm 3In a plastic container, 0.5 parts of acetylene black (Denka Black (registered trademark) HS-100, manufactured by Denka) as a conductive assistant, 1 part of carboxymethylcellulose (Carboxymethylcellulose #1190, manufactured by Daicel FineChem, non-volatile content 100%, hereinafter abbreviated as "CMC") as a thickener, and 32.5 parts of water were mixed, and then stirred for 30 seconds at 2,000 rpm using a centrifugal mixer (Thinky Corporation's Awatori Rentaro, ARE-310). Thereafter, 97 parts of lithium iron phosphate HED (trademark) LFP-400, manufactured by BASF, non-volatile content 100%, hereinafter abbreviated as "LFP") was added as a positive electrode active material, and the mixture was stirred for 150 seconds at 2,000 rpm using the mixer. Then, 2.5 parts of PTFE (polytetrafluoroethylene Polyflon PTFE D-210C manufactured by Daikin Industries, Ltd., non-volatile content 60 mass%, hereinafter abbreviated as "PTFE") was added as a binder, and the mixture was stirred at 2,000 rpm for 30 seconds using the above mixer to obtain a composite slurry for a non-aqueous secondary battery positive electrode.

[0101] The obtained standard positive electrode composite slurry was applied to an aluminum foil with a thickness of 20 μm as a current collector using an applicator, and then dried in an electric oven at 120°C ± 5°C for 25 minutes to obtain an electrode with a coating weight per unit area of ​​20 mg / cm. 2 Further, a rolling process was performed using a roll press (Thank Metal, 3 ton hydraulic roll press) to adjust the density of the composite layer to 2.1 g / cm. 3 A standard positive electrode was prepared.

[0102] (Secondary battery production) [Example Z-1] The negative and positive electrodes shown in Table 3 were punched out to 50 mm x 45 mm and 45 mm x 40 mm, respectively, and a separator (porous polypropylene film (Celgard #2400)) was inserted between them into an aluminum laminate bag and dried at 70°C for 1 hour in an electric oven. After that, 2 mL of electrolyte was injected into a glove box filled with argon gas, and the aluminum laminate was sealed to prepare a laminated nonaqueous secondary battery. The electrolyte used was a 1M solution of LiPF6 using a mixed solvent of 48 parts ethylene carbonate, 52 parts diethyl carbonate, and 1 part vinylene carbonate.

[0103] [Examples Z-2 to 47, Comparative Examples Z-1 to 11] Except for changing the configuration shown in Table 3, a nonaqueous secondary battery was obtained in the same manner as in Example Z-1.

[0104] Battery evaluation (Rate characteristics) The obtained secondary battery was placed in a thermostatic chamber at 25°C, and charge / discharge measurements were performed using a charge / discharge device (Hokuto Denko, SM-8). After constant current / constant voltage charging (cutoff current 1mA (0.02C)) at a charge current of 10mA (0.2C) and a charge end voltage of 4.3V, constant current discharging was performed at a discharge current of 10mA (0.2C) and a discharge end voltage of 3V. After repeating this operation three times, constant current / constant voltage charging (cutoff current (1mA (0.02C))) was performed at a charge current of 10mA (0.2C) and a charge end voltage of 4.3V, and constant current discharging was performed at discharge currents of 0.2C and 3C until the discharge end voltage reached 3.0V, and the discharge capacity was calculated for each. The rate characteristics were calculated based on the ratio of the 0.2C discharge capacity to the 3C discharge capacity, as shown in the following formula 1. (Formula 1) Rate characteristic = 3C discharge capacity / 3rd 0.2C discharge capacity × 100 (%) Judgment criteria ◎: Rate characteristics are 80% or more. Extremely good. ○: Rate characteristics are 70% or more and less than 80%. Good. △: Rate characteristics are 60% or more and less than 70%. Usable. ×: Rate characteristics are less than 60%. Not usable.

[0105] (Cycle characteristics) The obtained secondary battery was placed in a constant temperature room at 25°C, and charge / discharge measurements were performed using a charge / discharge device (SM-8, manufactured by Hokuto Denko). After constant current / constant voltage charging (cutoff current 2.5mA (0.05C)) was performed with a charge current of 25mA (0.5C) and a charge end voltage of 4.3V, constant current discharging was performed with a discharge current of 25mA (0.5C) and a discharge end voltage of 3V. This operation was repeated 200 times. The cycle characteristics were calculated based on the ratio of the 3rd 0.5C discharge capacity at 25°C to the 200th 0.5C discharge capacity, as shown in the following formula 2. (Formula 2) Cycle characteristic = 3rd 0.5C discharge capacity / 200th 0.5C discharge capacity × 100 (%) Judgment criteria ⊚: Cycle characteristics are 85% or more. Extremely good. ◯: The cycle characteristic is 80% or more and less than 85%. Good. △: The cycle characteristic is 75% or more and less than 80%. Usable. ×: Cycle characteristics are less than 75%. Unusable.

[0106] (High temperature characteristics) The obtained secondary battery was placed in a constant temperature room at 25°C, and charge / discharge measurements were performed using a charge / discharge device (Hokuto Denko, SM-8). After constant current / constant voltage charging (cut-off current 2.5mA (0.05C)) was performed with a charge current of 25mA (0.5C) and a charge end voltage of 4.3V, constant current discharging was performed with a discharge current of 25mA (0.5C) and a discharge end voltage of 3V. This operation was repeated 10 times, and then constant current / constant voltage charging (cut-off current 2.5mA (0.05C)) was performed with a charge current of 25mA (0.5C) and a charge end voltage of 4.3V. Thereafter, the battery was left standing in a constant temperature room at 70°C for 72 hours, and then left standing in a constant temperature room at 25°C for 1 hour, and constant current discharging was performed with a discharge current of 100mA (2.0C) and a discharge end voltage of 3V. The high temperature characteristics were calculated based on the ratio of the 10th 0.5C discharge capacity to the 11th 2.0C discharge capacity at 25°C (Equation 3 below). (Formula 3) High temperature characteristics = 2.0C discharge capacity / 10th 0.5C discharge capacity × 100 (%) The high temperature properties were evaluated according to the following four-level scale. ◎: High temperature properties are 60% or more. Extremely good. ○: High temperature properties are 55% or more and less than 60%. Good. △: High temperature properties are between 50% and 55%. Usable. ×: High temperature properties are less than 50%. Not suitable for use.

[0107] (Low temperature characteristics) The obtained secondary battery was placed in a constant temperature room at 25°C, and charge / discharge measurements were performed using a charge / discharge device (Hokuto Denko, SM-8). After constant current / constant voltage charging (cut-off current 2.5mA (0.05C)) was performed with a charge current of 25mA (0.5C) and a charge end voltage of 4.3V, constant current discharging was performed with a discharge current of 25mA (0.5C) and a discharge end voltage of 3V. This operation was repeated 10 times, and then constant current / constant voltage charging (cut-off current 2.5mA (0.05C)) was performed with a charge current of 25mA (0.5C) and a charge end voltage of 4.3V. The battery was then left to stand in a constant temperature room at -10°C for 1 hour, and constant current discharging was performed with a discharge current of 100mA (2.0C) and a discharge end voltage of 3V. The low temperature characteristics were calculated based on the ratio of the 10th 0.5C discharge capacity at 25°C to the 11th 2.0C discharge capacity, as shown in the following formula 4. (Formula 4) Low-temperature characteristics = 2.0C discharge capacity / 10th 0.5C discharge capacity × 100 (%) The low temperature properties were evaluated according to the following four-level scale. ◎: Low temperature properties are 70% or more. Extremely good. ○: Low temperature properties are 65% or more and less than 70%. Good. △: Low temperature properties are between 60% and 65%. Usable. ×: Low temperature characteristics are less than 60%. Not usable.

[0108] As shown in the table, the binder resin composition for non-aqueous secondary battery electrodes using the binder for non-aqueous secondary battery electrodes of the present invention is excellent in solution stability and coatability, and further, an electrode having a composite layer formed from the resin composition is extremely excellent in flexibility and adhesion. It was confirmed that by providing such a non-aqueous secondary battery electrode, a non-aqueous secondary battery having good rate characteristics, cycle characteristics, high temperature characteristics, and low temperature characteristics can be obtained.

[0109] [Table 3]

[0110] [Table 3]

[0111] [Table 3]

Claims

1. A binder for a non-aqueous secondary battery electrode, comprising a polymer (A1), the polymer (A1) being a polymer of an ethylenically unsaturated monomer mixture, the mixture comprising (meth)acrylamide and a nonionic ethylenically unsaturated monomer (a-1) having a logarithm of an octanol / water partition coefficient (Log Kow) at 25°C of 1.0 to 3.0, wherein when a mixed liquid consisting of ethylene carbonate and diethyl carbonate in a volume ratio of 2:3 at 25°C is deposited on a film made of the binder for a non-aqueous secondary battery electrode, the contact angle of 0.5 μL of the mixed liquid 1 second after the deposition is 5° to 40° at 25°C.

2. The binder for a non-aqueous secondary battery electrode according to claim 1, wherein the mixture contains, based on the total mass of the ethylenically unsaturated monomer mixture, 60 to 85 mass % of (meth)acrylamide and 15 to 40 mass % of a nonionic ethylenically unsaturated monomer (a-1) having a logarithm of an octanol / water partition coefficient (Log Kow) at 25° C. of 1.0 to 3.

0.

3. 3. The binder for a non-aqueous secondary battery electrode according to claim 2, wherein the mixture further contains 0.05 to 2 mass % of a reactive surfactant (a-2) having one or more unsaturated double bonds. (However, the above (a-2) excludes the above (a-1).)

4. 2. The binder for a non-aqueous secondary battery electrode according to claim 1, wherein the polymer (A1) has an acid value of 100 mgKOH / g or less.

5. The polymer (A1) has a storage modulus at 150° C. of 1.0×10 6 The binder for a non-aqueous secondary battery electrode according to claim 1 , wherein the viscosity of the binder is 100 Pa or more.

6. 6. A binder composition for a non-aqueous secondary battery electrode, comprising the binder for a non-aqueous secondary battery electrode according to claim 1 and a medium, wherein when a concentration of the polymer (A1) contained in the binder for a non-aqueous secondary battery electrode is 5 mass % in the composition, the binder composition for a non-aqueous secondary battery electrode has a transmittance at a wavelength of 400 nm of less than 70%.

7. A non-aqueous secondary battery electrode having a film containing the binder for non-aqueous secondary battery electrodes according to any one of claims 1 to 5.

8. A non-aqueous secondary battery comprising the non-aqueous secondary battery electrode according to claim 7.

Citation Information

Patent Citations

  • Power storage device binder aqueous solution, power storage device slurry, power storage device electrode, power storage device separator, power storage device separator / electrode laminate, and power storage device

    JP2023049937A

  • Slurry composition for negative electrodes of lithium ion secondary batteries, negative electrode for lithium ion secondary batteries, and lithium ion secondary battery

    WO2015064464A1

  • Binder composition for electrode of secondary battery, and electrode mixture

    WO2020096287A1

  • Binder for lithium secondary battery negative electrode, and lithium secondary battery negative electrode including same

    WO2021060737A1